Metal Artifact Reduction Magnetic Resonance Imaging Around Arthroplasty Implants: The Negative Effect of Long Echo Trains on the Implant-Related Artifact. Issue 5 (May 2017) - Kumar, Neil M.; de Cesar Netto, Cesar; Schon, Lew C.; Fritz, Jan
Abstract : Objectives: Long echo train length (ETL) is an often recommended but unproven technique to decrease metal artifacts on magnetic resonance imaging (MRI) scans. Therefore, we quantitatively and qualitatively assessed the effects of ETL on metal artifact on MRI scans using a cobalt-chromium–containing arthroplasty implant system. Materials and Methods: Using a total ankle arthroplasty system implanted into a human cadaver ankle and a clinical 1.5 T MRI system, turbo spin echo (TSE) pulse sequences were acquired with ETL ranging from 3 to 23 and receiver bandwidth (BW) from 100 to 750 Hz/pixel, whereas effective echo time and spatial resolution were controlled. A compressed sensing slice encoding for metal artifact correction TSE prototype pulse sequence was used as reference standard. End points included the total implant-related artifact area and implant-related signal void areas. Two raters evaluated the overall image quality and preference across varying BW and ETL. Two-factor analysis of variance, Friedman test, Kruskal-Wallis test, and Pearson correlation were used. P values of less than 0.05 were considered statistically significant. Results: The total implant-related artifact area ranged from 0.119 for compressed sensing slice encoding for metal artifact correction (BW, 600 Hz/pixel; ETL, 3) to 0.265 for TSE (BW, 100 Hz/pixel; ETL, 23). Longer ETL significantly increases the total implant-related artifact area ( P = 0.0004), whereas it decreased with increasing BW ( P < 0.0001). Implant-related signal void areas were not significantly affected by larger echo train length, but reduced with higher BW ( P < 0.0001). Readers had a significant preference for images with high BW and short ETL ( P < 0.0001). Conclusions: High receiver BW is the most effective parameter for reduction of arthroplasty implant-induced metal artifact on MRI scans, whereas in contradiction to prevalent notions, long echo trains fail to reduce implant-related metal artifacts, but in fact cause degradation of image quality around the implant with resultant larger appearing total metal artifacts.